Protecting the Community : a worker's guide to health and safety in Europe - Allen, Mike; Mather, Celia (London, 1992)
"UK health and safety law has been transformed by new regulations required by European Union directives. Protecting the Community explains how trade unionists can use European law. It looks at how governments try to influence, support or resist new regulation and how trade unions can play a part. It shows how cooperation with workers in Europe is vital for the future."